If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -42 = 4(2x + -3) Reorder the terms: -42 + 2x = 4(2x + -3) Reorder the terms: -42 + 2x = 4(-3 + 2x) -42 + 2x = (-3 * 4 + 2x * 4) -42 + 2x = (-12 + 8x) Solving -42 + 2x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -42 + 2x + -8x = -12 + 8x + -8x Combine like terms: 2x + -8x = -6x -42 + -6x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 -42 + -6x = -12 + 0 -42 + -6x = -12 Add '42' to each side of the equation. -42 + 42 + -6x = -12 + 42 Combine like terms: -42 + 42 = 0 0 + -6x = -12 + 42 -6x = -12 + 42 Combine like terms: -12 + 42 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 3(4x+4)=5x+40 | | -4x-2=-2x+0 | | -3x-30=-4x-34 | | 3(x+3)-10=-3x+35 | | -3x+47=3(4x-2)+8 | | 2x-33=5(4x-1)-10 | | 5x-32=-17 | | 1=3(x+3)-5 | | -39=3(x-5) | | 5(2x+5)=-2x+49 | | x+14=2(2x+2)+1 | | 2(5x+1)=5x-8 | | 4(x+2)-2=-x+41 | | 7=3(x+1)+1 | | B=5n+15 | | 8x+29=-2x-51 | | 3(x-2)+6=27 | | 9x-27=-36 | | 3(x+4)-5=28 | | x-35=4(3x+1)+5 | | 3x-2=3(2x-1)-5 | | -39=3(3x-4) | | -x-24=3(4x+5) | | 7+91r=39r+55 | | 4(x-1)+1=-19 | | 3x-40=3(3x+4)+8 | | 4x-6=5(x-4)+8 | | -x-14=4(3x+3) | | -8=2(2x+2) | | 4(3x-2)-8=3x+29 | | -15=5(x-2) | | -3x-26=2(2x-4)+3 |